Skema Aktan dalam alur cerita Novel 2 Barista karya Najhaty Sharma: Analisis naratologi A. J. Greimas - Almunazzah, Nuswah (Maliki Interdisciplinary Journal, 2024)
Literary works serve as reflections of society's life. Many life values can be extracted from a piece of literature, particularly novels. As in the novel titled "Dua Barista" by Najhaty Sharma, it contains implicit meanings related to religious, social, and cultural values. This study employs A.J. Greimas' narratology theory and utilizes a descriptive qualitative method, including Reading, Observing, and Notating Techniques, while applying the actant schema and Greimas' Functional Model. The research results reveal the presence of five actant schema patterns and functional models representing the overall narrative of the novel. Consequently, it is expected that readers can easily comprehend and grasp the story's narrative and the underlying meanings within the novel.